2011
DOI: 10.1007/s11121-011-0224-7
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Reproductive Work and Sociodemographic and Psychosocial Factors in Regard to Psychological Distress in Men and Women in Spain

Abstract: Studies have shown that some sociodemographic factors, such as marital status, employment status or social class, can affect mental health in different ways for each gender. However, up until now, few research projects have tried to ascertain if the role that reproductive work or psychosocial factors play in mental health is different for men and women. The aim of this study is to assess the differences between men and women in terms of how reproductive work, sociodemographic and psychosocial factors are linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Females and males in Spain and the United States had similar percentages of partial responses for CAS and CATA survey formats (Table 6). Ruiz-Pérez, Ricci-Cabello, Plazaola-Castaño, Montero-Piñar, and Escribá-Agüir (2011) reported that sociodemographic and psychological factors had no impact on the psychological distress of close to 30,000 men and women in Spain. Conversely, CAS data for females and males in Brazil, China, and India were found to have significantly higher percentages of incomplete responses.…”
Section: Comparison Of Survey Format Incompletion Ratesmentioning
confidence: 99%
“…Females and males in Spain and the United States had similar percentages of partial responses for CAS and CATA survey formats (Table 6). Ruiz-Pérez, Ricci-Cabello, Plazaola-Castaño, Montero-Piñar, and Escribá-Agüir (2011) reported that sociodemographic and psychological factors had no impact on the psychological distress of close to 30,000 men and women in Spain. Conversely, CAS data for females and males in Brazil, China, and India were found to have significantly higher percentages of incomplete responses.…”
Section: Comparison Of Survey Format Incompletion Ratesmentioning
confidence: 99%
“…The clinically meaningful primary trial outcomes were (a) walking speed, and (b) accelerometry-determined physical activity and sedentariness; these were supported by (c) observations of locomotor and sedentary behaviors (secondary outcomes). Finally, since both depression and poorer physical function/activity may be associated with psychosocial stress and low socioeconomic status in humans (Lorant et al 2003(Lorant et al , 2007Missinne and Bracke 2012;Ruiz-Perez et al 2011;Plouvier et al 2016;Brunner et al 2009), we constructed regression models to explain the variance in walking speed, total activity and sedentariness based on depression, anxiety, and social status.…”
Section: Introductionmentioning
confidence: 99%